BAHAN AJAR TEMATIK DALAM PELAKSANAAN KURIKULUM 2013 - Zaenol Fajri (Nurul Jadid University, 2018)
The curriculum 2013 emphasized on learning of an approach thematic basis, to solve Approach learning that integrate some competence and subject into various theme, so that a students primary school (SD/MI) are not learning this partial between the charge a lesson. Of an approach to a thematic basis, Influence on the use of the teaching materials, So teaching materials used is teaching materials thematic Teaching materials thematic completely consistent with 2013 curriculum and characteristic of students. The development level students are still at reflect holistic and concrete operational. Students could not understanding the concept of subjects when given separately, so the use of teaching materials thematic is very suitable for elementary school students (SD/MI)